Optimal Power Flow with Voltage-Sensitive Loads in Distribution Networks - Cerbantes, Marcel Chuma [UNESP]; Mantovani, José Roberto Sanches [UNESP]; Fernández-Blanco, Ricardo; Ortega-Vazquez, Miguel A. (Institute of Electrical and Electronics Engineers (IEEE), 2016)
Traditionally, the optimal power flow (OPF) assumes a constant (active and reactive) power load model and thus it neglects the effect of the voltage sensitiveness of power load injections. As a consequence, the results from the OPF may be distorted and lead to suboptimal solutions. This paper proposes an optimal power flow, which seeks to minimize the total active power losses of a distribution network with voltage-sensitive loads. The mathematical model is highly nonlinear and nonconvex due to the ac network constraints and the voltage-sensitive load models. A Tabu Search algorithm capable of handling the non-linearities associated with practical modeling aspects is proposed. Numerical results on a 69-bus distribution test system show the effectiveness of the proposed approach, as well as the impact of the load power injections on the voltage profile of the system.
Keywords: Distributed generation; Optimal power flow; Tabu Search algorithm; Voltage-sensitive loads